Forgiving and forgetting: Family Conflict Resolution through Customary Law among the Tolaki People of Southeast Sulawesi, Indonesia - Erens Elvianus Koodoh; Idaman Idaman; Danial Danial (Journal of Law, Social Science and Management, 2024)
Introduction: Southeast Sulawesi's Tolaki people have a system of customary law that is infused with local knowledge and values. In addition to governing day-to-day activities, Tolaki customary law offers advice on how to settle disputes, particularly those inside the family. In reality, Tolaki customary law places a strong emphasis on the idea of forgetting and forgiving as the primary method of resolving disputes. The phrase "Mo’ambongi ronga Monggolupe," which translates to "forgive and forget," reflects this idea. This approach is the foundation of conflict resolution, promoting peace and reconciliation amongst warring family members. Objectives: The purpose of this study is to investigate how Tolaki customary law's concept of "forgiving and forgetting" might be applied to family disputes and how it affects social relationships within the Tolaki community. Method: This study is qualitative in nature. Documentation and in-depth interviews are among the data used. Qualitative data analysis was then used to examine the findings from the primary source, which are in-depth interviews. Result: The study's findings indicate that there are two types of family conflict (sisala'a) among the Tolaki people in Konawe Regency: open conflict and closed conflict. Fights between siblings and cousins are common examples of open confrontations. The extended family is involved in this situation. If left unaddressed, open arguments like these might turn into fights or more serious conflicts like disputes between villages. When a dispute is closed, there is a disruption in contact, which shows up as a lack of pleasantries and greetings. Conclusion: Local government, religious leaders, and traditional leaders all play a role in resolving family disputes among the Tolaki people. Kalo is the mechanism by which this issue is resolved. Keywords: Family Conflict; Customary Law; Tolaki People; Indonesia